DAMPAK PEMIKIRAN KRITIS DAN KEMAMPUAN ANALITIS PADA PEMAHAMAN NILAI-NILAI PANCASILA - Safaruddin (Pojok Publisher, 2025)
This study focuses on the relationship between critical thinking, analytical skills, and understanding of Pancasila values. Using a quantitative approach, this study aims to measure the influence of these two variables on the understanding of Pancasila. Data were collected from 60 respondents through questionnaires. To analyze the data, this study used multiple linear regression analysis. This is a statistical method that allows researchers to measure the combined impact of several independent variables (in this case, critical thinking and analytical skills) on one dependent variable (understanding of Pancasila). The results indicate that both independent variables, both separately (partially) and together (simultaneously), have a significant influence on the understanding of Pancasila values. This finding is supported by statistical tests, namely the F-test (simultaneous test) and the t-test (partial test), which show strong significance values. Thus, the results of this study confirm that critical thinking and analytical skills are crucial in forming a deep understanding of Pancasila. Having these two skills allows one to not only memorize but also understand and internalize the fundamental values ​​of the Indonesian nation more effectively.